A porous organic polymer supported Pd/Cu bimetallic catalyst for heterogeneous oxidation of alkynes to 1, 2-diketones. Issue 3 (18th January 2022) - Song, Jiaxin; Zhang, Kai; Huang, Zhongye; Zhao, Jinyu; Yang, Zhengyi; Zong, Lingbo; Chen, Jianbin; Xie, Congxia; Jia, Xiaofei
Abstract : A reusable Pd/Cu bimetal-loaded porous organic polymer (Pd/Cu@POP–POPh3 ) has been developed for heterogeneous oxidation of various alkynes to afford the corresponding 1, 2-diketones in high to excellent yields. Abstract : A porous organic polymer (POP–POPh3 ) was readily prepared by oxidation of POP-PPh3 with H2 O2 . After coordination with PdCl2 and a co-catalyst of a CuBr2 precursor, a Pd/Cu bimetal-loaded porous organic polymer (Pd/Cu@POP–POPh3 ) was afforded. The NMR and XPS characterizations indicated that both Pd(ii ) and Cu(ii ) could coordinate with the PO bonds in the polymer. Furthermore, the catalyst has high surface areas, hierarchical porosity and good thermostability. The Pd/Cu@POP–POPh3 catalyst was successfully used in heterogeneous oxidation of alkynes with O2 as the oxidant to afford corresponding 1, 2-diketones in high to excellent yields (76–99%). A series of alkynes with various functional groups performed well in the process. Remarkably, the heterogeneous catalyst can be reused for five cycles without significant loss of catalytic activity in oxidation of diphenylacetylene.